Further analysis on cardiovascular wall mechanics with MRI postprocessing approaches: wall shear stress in aorta with coarctation and myocardial systolic strain in the left ventricle - Chen, Maria Manuela Zhu (2016)
Tese de mestrado integrado em Engenharia Biomédica e Biofísica, apresentada à Universidade de Lisboa, através da Faculdade de Ciências, 2016